Fintech in Europe and Central Asia Maximizing Benefits and Managing Risks - Berg, Gunhild (The World Bank, 2020)
FinTech has tremendous potential in the Europe and Central Asia (ECA) region, given its high mobile phone and internet access levels and scope for increased use of digital payments. However, there are major regional differences between high-income and middle-income countries regarding access to technology, FinTech adoption, and regulatory capacity. This paper analyzes the opportunities and risks related to FinTech in the ECA region, focusing on these three key financial sector challenges: (i) high costs of international remittances, (ii) inefficiencies in the provision of domestic payments, and (iii) low levels of MSME's access to finance. It also analyzes the level of FinTech development in the region, and delves into the state of FinTech policy, regulation and supervision in the region along with an analysis of reform needs. Finally, this paper touches upon the role for international public policy coordination related to FinTech generally, with a focus on the ECA region